A Practical Guide to Quality Interaction with Children who Have a Hearing Loss. - Clark, Morag (Plural Publishing, Inc., 2006)
This book is a practical guide for those seeking to lead children with hearing impairment to fluent intelligible spoken language by engaging in quality interaction at the language learning stage.